Generalization of the Hamilton-Jacobi approach for higher-order singular systems - Pimentel, B. M.; Teixeira, R. G. (Editrice Compositori Bologna, 1998)
We generalize the Hamilton-Jacobi formulation for higher-order singular systems and obtain the equations of motion as total differential equations. To do this we first study the constraints structure present in such systems.